Zastosowanie koncepcji benchmarkingu w sferze logistyki - Dąbrowska-Mitek, Magdalena (Application of benchmarking in logistics, 2007)
Benchmarking is a tool, that is known and used in many enterprises from many years (especially in firms, that were organized in frames of market conditions). Its main idea is to equal the best practice world. This idea has influence not only on organization development, but also on whole economy development. In the paper, the author presents practical aspects of using benchmarking in logistics. The author of this article points potential benefits of application of logistics processes benchmarking based on Porter’s chain of values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 349-360